2013
DOI: 10.1039/c3nr33421j
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of photobleaching, oxidation and metal induced fluorescence quenching of DNA-templated silver nanoclusters

Abstract: Such metal induced quenching cannot be recovered by NaBH4. Electronic absorption and mass spectrometry studies offered further insights into the oxidation reaction. Our results correlate many important experimental observations and will fuel the further growth of this field.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 55 publications
(45 reference statements)
6
55
0
Order By: Relevance
“…The same trend of sensitivity was observed with light exposure, which is related to oxidation of the AgNCs [73]. It has been concluded that metal ions (usually Hg 2+ , Cu 2+ , Ag + and Au 3+ ) can quench metal NCs due to their high redox potential.…”
Section: Reactive Quencherssupporting
confidence: 58%
See 1 more Smart Citation
“…The same trend of sensitivity was observed with light exposure, which is related to oxidation of the AgNCs [73]. It has been concluded that metal ions (usually Hg 2+ , Cu 2+ , Ag + and Au 3+ ) can quench metal NCs due to their high redox potential.…”
Section: Reactive Quencherssupporting
confidence: 58%
“…We found that DNA templated AgNCs were bleached very quickly when exposed to strong light. A wavelength-dependent study indicates that photobleaching takes place only by the UV light, while little effect was observed at wavelengths longer than 400 nm [73]. We attributed photobleaching to oxidation since bleached AgNCs can be recovered after adding NaBH4.…”
Section: Characterization Of Ncsmentioning
confidence: 90%
“…[ 6 ] Not all AgNCs have such excellent chemical and photostability, especially in solution. [ 20,38 ] The fl uorescence decay times are calculated every 10 000 photons and plotted alongside the fl uorescence trajectory (Figure 1 a). Of the 289 C24-AgNCs measured, the overwhelming majority could be fi tted with a monoexponential decay function (285 of 289, 99%).…”
Section: Single Molecule Measurements: Decay Timesmentioning
confidence: 99%
“…Many research groups including our own showed that photobleaching of AgNCs is related to oxidation. [33][34][35] In this regard, AuNC might be a useful alternative since gold is more resistant to oxidation than silver. While adsorption of DNA by gold nanoparticles (AuNPs) have been extensively studied since the 1990s, [36][37][38][39][40] using DNA for making AuNCs has been reported only very recently.…”
Section: Introductionmentioning
confidence: 99%